Peran Mahasiswa GIAT UNNES Dalam Pendampingan Usaha Kecil Menengah (UMKM) Pete di Desa Sambeng - Jauharul Ulum; Khairul Dama Setiadi; Roihanatussahla Roihanatussahla; Ni Komang Dilla Ayu Puspa Rini; Ema Agita Yulianti (Universitas Negeri Semarang, 2024)
This article explores the significant role played by students from Universitas Negeri Semarang's (UNNES) Community Service Program (GIAT) in supporting and empowering pete Small and Medium Enterprises (UMKM) in Sambeng Village. By adopting a structured methodology that includes assessment, collaborative planning, skill development, and continuous monitoring, the UNNES GIAT students have facilitated improvements in production processes, product quality, and marketing strategies for the UMKMs. This collaborative partnership not only highlights the potential of academia-industry collaboration but also emphasizes the importance of grassroots initiatives in driving sustainable economic development and community engagement.